104 MASQUERADER OF MALARIA-BABESIOSIS. (1st January 2006) - Atwal, P.; Godkar, D.; Atwal, C.; Niranjan, S.
Abstract : Background: Babesiosis is a tick-borne illness caused by malaria-like protozoa that infects red blood cells resulting in hemolysis. Patients typically present with fever, chills, fatigue, and history of a tick bite or travel to an endemic area. Laboratory studies reveal hemolytic anemia, thrombocytopenia, and atypical lymphocyte formation. The clinical presentation and peripheral blood smear appear similar to malaria. A definitive diagnosis can be made from a peripheral blood smear, which may show the presence of exoerythrocytic parasites, the classic appearance of tetrads of merozoites forming "Maltese crosses. " Two-drug regimens are currently favored for the treatment of babesiosis, atovaquone-azithromycin, or quinine-clindamycin. Exchange transfusion is often used as adjunctive therapy in patients with severe hemolysis, HIV, and high parasitemia (> 10%). Case Report: A 45-year-old Mexican male, in the United States for 10 years with recent travel to Long Island (Hamptons), presented with fever, chills, fatigue, and headache. Laboratory data revealed hemolytic anemia and thrombocytopenia. The peripheral blood smear showed intraerythrocytic parasites with 6-7% parasitemia, resembling falciparum malaria. Serologic testing with IFAT was positive for both IgG and IgM against babesial antigens. PCR was positive for parasitemia. The patient was successfully treated with oral atovaquone and Zithromax, as demonstrated by clinical improvement and gradual disappearance of parasitemia in the peripheral smear. Teaching Point: In patients presenting with a malaria-like illness and no recent travel outside the United States, babesiosis must be considered in the differential diagnosis.